Giant smooth muscle hamartoma. - Bombonato, C.; Mapelli, E.T.M.; Colombo, L.; Gualandri, L.; Boccardi, D.; Moneghini, L.; Menni, S. (European Journal of Pediatric Dermatology, 2011)
Smooth-muscle hamartoma classically presents as a small hairy, skin-colored patch or plaque. Rare cases with diffuse involvement have been described. Here is reported a largesized case of smooth muscle hamartoma.